Differences In Consumers’ Attitude Towards Online Shops Based On Product Types And Consumer Characteristics And Their Influence On Repurchase Interests - Ike Janita Dewi; Odilia Larasati Hertaswari (Jurnal Manajemen Indonesia, 2021)
The research responds to the new realities in marketing environment following the rapid development of internet and information technology. In accordance with Yadav and Pavlou’s (2014) new research directions in computer-mediated environments, this research examines the relevance of market segmentation in online distribution strategies. Specifically, this research aims at analyzing: (1) the difference in consumers’ attitudes towards online shops based on consumers’ demographic and behavioral characteristics, (2) the difference in consumers’ attitudes towards online shops depending on product type sold by the online shops, and (3) influence of attitude towards online shops on repurchase intentions. Data were collected using online and offline questionnaire to 200 respondents. Data analysis techniques include Analysis of Variance, multiple comparison, and simple linear regression. Results of the research show that demographic (gender and age) and behavioral (frequency of purchase) segmentation variables can generally explain differences in consumers’ attitude towards online shops. Differences in consumers’ attitudes are also shown in the cases of different product types (gadgets versus fashion) sold in the online shops. Lastly, consumers’ attitudes positively affect repurchase intention. Keywords— attitude; computer-mediated consumer behavior